Pitx1 determines characteristic hindlimb morphologies in cartilage micromass culture. - Natalie C Butterfield; Chen Qian; Malcolm P O Logan (PLoS ONE)
The shapes of homologous skeletal elements in the vertebrate forelimb and hindlimb are distinct, with each element exquisitely adapted to their divergent functions. Many of the signals and signalling pathways responsible for patterning the developing limb bud are common to both forelimb and hindlimb. How disparate morphologies are generated from common signalling inputs during limb development remains poorly understood. We show that, similar to what has been shown in the chick, characteristic differences in mouse forelimb and hindlimb cartilage morphology are maintained when chondrogenesis proceeds in vitro away from the endogenous limb bud environment. Chondrogenic nodules that form in high-density micromass cultures derived from forelimb and hindlimb buds are consistently different in size and shape. We described analytical tools we have developed to quantify these differences in nodule morphology and demonstrate that characteristic hindlimb nodule morphology is lost in the absence of the hindlimb-restricted limb modifier gene Pitx1. Furthermore, we show that ectopic expression of Pitx1 in the forelimb is sufficient to generate nodule patterns characteristic of the hindlimb. We also demonstrate that hindlimb cells are less adhesive to the tissue culture substrate and, within the limb environment, to the extracellular matrix and to each other. These results reveal autonomously programmed differences in forelimb and hindlimb cartilage precursors of the limb skeleton are controlled, at least in part, by Pitx1 and suggest this has an important role in generating distinct limb-type morphologies. Our results demonstrate that the micromass culture system is ideally suited to study cues governing morphogenesis of limb skeletal elements in a simple and experimentally tractable in vitro system that reflects in vivo potential.